HUBUNGAN ANTARA MEDIA PEMBELAJARAN INTERAKTIF DENGAN HASIL BELAJAR PENDIDIKAN PANCASILA SISWA KELAS IV SD NEGERI 3 DELOD PEKEN - Ni Putu Heny Purbayanti; I Wayan Suyanta; Kd Jayanthi Riva Prathiwi (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2026)
This study examined the correlation between the use ofPowerPoint-based interactive learning media and Pancasila Education learning outcomes among fourth-grade students atSD Negeri 3 Delod Peken, Tabanan. A quantitativecorrelational design was employed involving 48 studentsselected through saturated sampling. Data were collectedusing questionnaires and document studies, then analyzedthrough descriptive statistics and the Pearson Product Momentcorrelation test. The results revealed a significant positivecorrelation (r = 0.741, p = 0.001), indicating that interactivePowerPoint media contributed to better learning outcomes. The media also enhanced students’ focus, participation, andmotivation during classroom learning.